Analysis of Dominant Factors That Influence Public Dissatisfaction Indonesia In Service Public: Studies Meta- Analysis - Tia; Helmy; Aldy (IFADAH : Jurnal Ekonomi Dan Bisnis Syariah, 2026)
Public service dissatisfaction in Indonesia persists despite regulatory advances like Law No. 25/2009 and SPBE Presidential Regulation No. 95/2018, which aligns with New Public Service (NPS) principles emphasizing citizen-centered governance. This meta-analysis study identifies dominant factors influencing public dissatisfaction through a systematic literature review (SLR) and meta-analytic synthesis of empirical studies from 2019–2025. Following PRISMA guidelines, we searched databases (eg, Google Scholar) using keywords like "Indonesian public service dissatisfaction," screened for inclusion (peer-reviewed articles with empirical data on Indonesian public services), and analyzed quantitative (eg, effect sizes via IKM and SERVQUAL dimensions) and qualitative data. Results reveal five dominant factors: low responsiveness and speed, bureaucratic complexity, suboptimal civil servant quality, weak empathy and ethics, and ineffective technology utilization. Meta-analysis shows responsiveness and reliability as the strongest negative predictors of satisfaction (significant effect sizes, p < 0.05), consistent across sectors like population administration, health, and licensing. These systemic issues reflect a failure to shift from hierarchical paradigms to NPS-oriented reforms. This study contributes theoretically to NPS by highlighting multidimensional barriers, offering policymakers evidence-based recommendations for holistic reforms in capacity building, cultural transformation, and user-centered digitalization to enhance democratic legitimacy and public trust.